Emotional Expression in Malory's Elaine of Ascolat - Holbrook, Sue Ellen (Parergon, 2007)
Shrieks and complaints, accompanied by body language, contribute markedly to Malory's representation of Elaine of Ascolat's emotionality. Elaine's two shrieks echo Lancelot's and indicate change from sorrow for a wounded beloved to heartbreak when he rejects her. When Elaine is compared with speakers in love lyrics, allegories, and romances, the thoughts in her unarticulated complaints after the pained second shriek may be understood and related to her defence of complaint and perseverance in love despite rejection. Similarly, Elaine's complaint letter, including its overlooked moan to ladies, reflects a state of tranquility and brings about a just resolution.
Keywords: dept.eng